0
$\begingroup$

So lately I have observed the following video:

https://www.youtube.com/watch?v=Ux7vl6zXxj0&t=6s

The nice fellow on this video explained why this following property is correct $$\frac{1}{1-x}=1+x+x^2+x^3+x^4...=\sum_{n=0}^{\infty}x^n$$ as long as $|x|<1$

I did not quite understand two things:

1.the long devisioning he did in order to get the power seirie from the fraction of one over X minus one

2.why is it true only if $|x|<1$, why does this condition apply?

Thanks for your assistance :)

$\endgroup$
  • $\begingroup$ If $|x|\ge1$ then $|x^n|\not\to0$ so the series diverges. $\endgroup$ – Lord Shark the Unknown Aug 10 '17 at 15:11
0
$\begingroup$

The video is not very rigorous, which is why you aren't able to determine why $|x|<1$ is needed. The series $\sum_{n=0}^\infty x^n$ really just means $$\lim_{n\to\infty}(1+x+x^2+\cdots+x^n).$$ Clearly this limit does not exist if $x=1$. Suppose $x\ne 1$. We attempt to show that this limit is equal to $1/(x-1)$ by showing that $$ \lim_{n\to\infty}\left| (1+x+\cdots+x^n)-\frac{1}{1-x} \right|=0. $$ Note that for any $n$, we have $$ \left| (1+x+\cdots+x^n)-\frac{1}{1-x} \right| = \left|\frac{1}{1-x}\right||(1-x)(1+x+\cdots+x^n)-1|$$ $$ = \left|\frac{1}{1-x}\right||(1+x+\cdots+x^n)-(x+x^2+\cdots+x^{n+1})-1|$$ $$= \left|\frac{1}{1-x}\right||-x^{n+1}| = \left|\frac{1}{1-x}\right||x|^{n+1}. $$ Now $|x|^{n+1}$ goes to $0$ as $n$ approaches infinty if and only if $|x|<1$. In conclusion $$\sum_{n=0}^\infty x^n = \frac{1}{1-x}$$ if and only if $|x|<1$.

$\endgroup$
0
$\begingroup$

I do not like the video much, so I will give you hints to understand this property by your own in a very easy and nice way.

Let us set $S_N= \sum_{n=0}^N x^n$ for $N\in \mathbf N$ and lets consider $|x|<1$. Just follow my three steps.

Step 1: Proof $S_N (1-x) = 1-x^N$ (telescop sum).

Step 2: Divide by $1-x\neq 0.$

Step 3: Calculate the limit $N\to \infty$ (and do not forget the definition of a series).

$\endgroup$
0
$\begingroup$

The basic identity, true for any $x$ and positive integer $n$ is that $(1-x)\sum_{k=0}^{n-1} x^k =1-x^{n} $. This is readily proved by induction.

Therefore, if $x \ne 1$, $\sum_{k=0}^{n-1} x^k =\dfrac{1-x^{n}}{1-x} =\dfrac{1}{1-x}-\dfrac{x^{n}}{1-x} $ or $\dfrac{1}{1-x}-\sum_{k=0}^{n-1} x^k =\dfrac{x^{n}}{1-x} $.

I will now show that if $0 < x < 1$ then $x^n \to 0$ and if $ x > 1$ then $x^n \to \infty$. The case $x < 0$ is handled by replacing $x$ by $-x$ and writing $\dfrac{1}{1+x}-\sum_{k=0}^{n-1} (-1)^kx^k =\dfrac{(-1)^nx^{n}}{1+x} $.

Note: What follows is not original.

The basic inequality used is Bernoulli's, which states that $(1+a)^n \ge 1+na $ if $a \ge 0$ and $n$ is a positive integer. This is readily proved by induction.

If $x > 1$ then $x = 1+y$ where $y > 0$. Therefore $x^n =(1+y)^n \ge 1+ny \gt ny$ and this $\to \infty$ as $n \to \infty$ for any $y > 0$.

If $0 < x < 1$, then $x = \dfrac1{1+y}$ where $y =\dfrac1{x}-1 $ satisfies $y > 0$. Therefore $x^n =\dfrac1{(1+y)^n} \le \dfrac1{1+ny} \lt \dfrac1{ny} \to 0 $ as $n \to \infty$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.